Analisis Konsep Panggilan dan Visi dalam Kepemimpinan Kristen - Sinah, Pace Aprisal; Sinah, Pace Aprisel (JURNAL LUXNOS, 2025)
Essential Christian leadership is a sacred grace and responsibility that functions as a representation of Christ, rooted in two pillars: Divine Calling and Prophetic Vision. Calling is the ontological foundation that emphasizes character integrity and service, answering the question "Who am I and for whom do I lead?". Meanwhile, Vision is the teleological compass, which is God's revelation regarding the long-term purpose, answering "Where are we going?". The alignment of both should result in deep spiritual transformation and tangible social impact. However, this idealism often clashes with contemporary reality, marked by a crisis of character integrity (moral scandals and abuse of power) and a drought of prophetic vision, where leaders are trapped in managerial routines. This gap indicates the fading understanding and implementation of Calling and Vision as a cohesive unit. The originality of this research lies in its novel theological-strategic synthesis. The method employed is Qualitative Library Research with a Theological-Conceptual Analysis approach. Previous studies tend to discuss Calling (character) and Vision (strategy) separately. This study explicitly analyzes how Calling must give birth to Prophetic Vision as a strategic manifestation of obedience. The aim is to present a Holistic Transformational Leadership Model as a practical guide to bridge the gap between biblical idealism and the complexities of leadership demands on the ground, in order to maximize the impact of God's Kingdom.